Comparison between the Effect of Closed Kinetic Chain and Open Kinetic Chain exercises in the strengthening of Vastus Medialis Obliqus in subjects with Patello-Femoral Pain Syndrome - a randomized control trial - Misbah Mustafa, Ishrat Fatima, Afeera Tariq, Muhammad Irfan Fazal, Muhammad Nauman Jamal, Ahmad Humayun Sarfraz (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the effects of closed kinetic chain and open kinetic chain exercises in the strengthening of vastus medialis obliqus in subjects with Patello-femoral pain syndrome. Methods: The study was a randomized controlled trial. It was conducted to compare the impact of open and closed kinetic chain exercises to strengthen the Vastus medialis obliqus in PFPS patients. For this purpose, 36 patients both males and females with age 20-40 years having PFPS were allocated randomly to two experimental (group A and group B) and one control group C. Group A, practised open kinetic chain exercises and the second group B practiced closed kinetic chain exercises, the control group C was given general physical therapy exercises, for four weeks. The assessment of Pain and function of the individual taking part in this study were was done before starting the treatment, at 2 weeks and at 4 weeks, using Numerical Pain rating scale and Kujala Anterior knee pain scale, respectively. Results: In conclusion, significant changes i.e. in alleviating pain and enhancing overall functionality has been seen in Group B that performed closed kinetic chain exercises for about 4 weeks. Similarly, there was also a remarked change in pain reduction besides improved function in group A and group C. By comparing all the three groups, significant advantage has been noted with closed kinetic chain exercises as compared to open kinetic chain and conventional PT techniques. Conclusion: Although, both exercise regimens were significant in pain reduction and enhancing function, but close kinetic chain exercises produced remarkable effects.